New Trends in Supercritical Fluid Technology and Pressurized Liquids for the Extraction and Recovery of Bioactive Compounds from Agro-Industrial and Marine Food Waste - Horacio Fraguela-Meissimilly; José Miguel Bastías-Monte; Claudia Vergara; Jaime Ortiz-Viedma; Roberto Lemus-Mondaca; Marcos Flores; Pamela Toledo-Merma; Sylvia Alcázar-Alay; Manuela Gallón-Bedoya (Molecules, 2023)
Growing consumer interest in healthy foods has led to an increased demand for bioactive compounds derived from eco-technologies. This review highlighted two emerging technologies, pressurized liquid extraction (PLE) and supercritical fluid extraction (SFE), which are based on clean processes aimed at recovering bioactive compounds from different food sources. We studied how the different processing conditions provide many advantages and a great opportunity to obtain compounds with antioxidant, antibacterial, antiviral, or antifungal activity from plant matrices and industrial biowaste, especially antioxidant compounds (anthocyanins and polyphenols) due to their important role in health promotion. Our research was conducted through a systematic search in different scientific databases related to the PLE and SFE topics. The review analyzed the optimal extraction conditions using these technologies, which lead to the efficient extraction of bioactive compounds, the use of different equipment, and recent combinations of SFE and PLE with other emerging technologies. This has given rise to the development of new technological innovations, new commercial applications, and the detailed recovery of various bioactive compounds extracted from different plant and marine life food matrices. These two environmentally friendly methodologies are fully valid and have great future application prospects in biowaste valorization. They represent a feasible technological tool that can promote the implementation of a circular economy model for the food industry. The underlying mechanisms of these techniques were discussed in detail and supported by current literature.